Hubungan Antara Kelekatan Teman Sebaya Dengan Stress Akademik Pada Siswa Kelas XII Jurusan MIPA Di SMAN X Padang - Kurniawan, Harri; Titisemita, Ane; Handayani , Sari; Susanti , Elva; Fenia , Selvi Zola (Jurnal Ekonomika Dan Bisnis (JEBS), 2021)
This study aims to determine the relationship between peer attachment and academic stress in class XII students majoring in Mathematics and Natural Sciences in SMAN X Padang. The independent variable in this study is peer attachment and the variable used is Academic Stress. Measuring instruments used in this research are peer attachment scale and Academic Stress. The sampling technique in this study used the Random Sampling technique. The sample in this study were 152 students at SMAN X Padang. The validity and reliability test in this study uses the Cronbach Alpha technique. The results of the validity coefficient on the stickiness scale of peers move from rix = 0.310 to rix = 0.809 with a reliability coefficient of α = 0.883 while on the academic stress scale moves from rix = 0.316 to rix = 0.803 with a reliability coefficient of α = 0.864. Based on data analysis, a decent value of -0,591 is obtained with a significance level of 0,000, which means the hypothesis is accepted. This shows that there is a significant relationship between peer attachment and academic stress of students at SMAN X Padang. While the effective contribution of the variable peer attachment to academic stress 35%.